THE EFFECT OF USING SOCIAL MEDIA BY BRANDS ON CUSTOMER ENGAGEMENT: CONTENT QUALITY, PERSONALIZATION, AND CONSTANT PRESENCE AS KEY FACTORS - Bouaddi, Mohamed; Sanaa, Mekdad; Siham, Khaldi (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This study investigates the impact of social media usage by companies on customer engagement, focusing on three key constructs: Content quality, personalized communication, and constant Presence. Employing a quantitative research methodology, data were collected through a structured survey distributed from mid-September to mid-October, yielding a sample that facilitated analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that high-quality content significantly enhances customer engagement, aligning with the notion that engaging and relevant material fosters trust and loyalty. Furthermore, personalized communication was also found to be critical, as tailored messages resonate with consumers and contribute to stronger relationships. Additionally, a constant presence on social media emerged as essential for maintaining engagement, reinforcing brands' accessibility and responsiveness. The study underscores the importance of integrating these elements into social media strategies to cultivate deeper customer connections and drive long-term loyalty in an increasingly competitive digital landscape.